A Critical Analysis of The Funeral Speeches in Shakespeare's Julius Caesar Using Principles of Rhetoric - Alabi, Adesanya M. (International Journal of Language and Literary Studies, 2024)
Julius Caesar is among William Shakespeare's most engrossing dramatic tragedies. Power, death, and life in its widest sense are all critically analysed in the play. Although tragedy is a highly sentimental literary genre, tragic plays typically evoke intense emotions in readers or viewers. Also, the art of rhetoric is a significant tool of persuasion that gives depth to the text. Drawing on Aristotle’s rhetorical concept, this study examines the rhetorical devices Shakespeare's characters in Julius Caesar employ to accomplish their objectives. However, the emphasis is on the distinctive characteristics of Mark Antony and Brutus, respectively, and how they effectively applied language to grab the attention of the Roman audience. It is evident by examining the rhetorical s devices used by the two powerful orators, Brutus and Mark Antony, that they apply different strategies and tactics to express their ideas and emotions to their audience. Their speeches particularly benefit from their proficiency in rhetoric. As the study progresses, it becomes more evident how each character presents their point of view and persuades others.